A comparative study of corrosive-erosive effects at AISI D3 steel, 304 stainless steel and CrN/AlN material (2012)
Corrosive-erosive effect on AISI D3 steel, 304 stainless steel and CrN/AlN coating in aqueous NaCl slurries was studied. CrN/AlN multilayer films with a thickness of 3 µm and bilayer period of Λ = 60 nm (50 bilayers) were obtained by using the physical vapor deposition (PVD) technique (magnetron sputtering). The corrosion-erosion experiments were performed in a test machine in which the impingement velocity, impact angle, concentration of solids and pH of the solution were controlled. Polarization curves were simultaneously obtained to correlate the electrochemical effects to the erosive wear mechanisms. The slurry used consists of silica particles suspended in a mixture of acid solution and 3.5% NaCl, with a pH value of 5.6. Electrochemical results showed the best corrosion resistance for 304 stainless steels. Additionally, the surface analysis by SEM micrograph revealed formation of cracks in CrN/AlN multilayers coating and plastic deformation in both steel substrates (AISI D3 steel, 304 stainless steel), especially when the mean impact angle is a critical value of 90°. Measurements of critical and passive current densities showed that the behavior of coated materials differed depending on the substrate that is used. Nonetheless, in a general way, by increasing the impact angle and by changing its incidence from normal to grazing, it led to a resistance to corrosion-erosion processes